MAKING MILK PIE WITH THE ADDITION OF DRAGON FRUIT (Hylocereus polyrhizus) IN LAMPISANG VILLAGE, PEUKAN BADA DISTRICT, ACEH BESAR REGENCY: PEMBUATAN PIE SUSU DENGAN PENAMBAHAN BUAH NAGA(Hylocereus polyrhizus) DI DESA LAMPISANG KECAMATAN PEUKAN BADA KABUPATEN ACEH BESAR - Kemalawaty, Mulla; Zulvia Maika Letis; Hayatun Nufus; Rachmat Hidayat; Chairil Anwar; Endiyani; Irhami; Sri Agustina; Aprita, Ika Rezvani (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2025)
Implementing Community Service (CS) activities aims to explain to the community how to use cow's milk and dragon fruit as complementary ingredients in making milk pie. A team of several students and lecturers conducted a situation analysis in the village to identify problems in the community. Based on the survey, the problem in the community is the low understanding and skills in processing cow's milk, even though its nutritional content is very high. The solution to this obstacle is to provide knowledge on how to process cow's milk into cake ingredients. The residents of Lampisang Village are very interested in the innovation of adding dragon fruit to milk pie, resulting in a cake that is more visually attractive and tastes more delicious. The result of this activity is that the community understands how to process cow's milk into milk pie by utilizing livestock milk and adding variations of dragon fruit flavors so that it can be practiced and has the potential to generate additional sources of income.